The Role of Mediator in Industrial Relationship Dispute Settlement Process during Covid-19 Pendemic at Labor Offices Department North Sumatra Province - Humaizi Humaizi; Munir Tanjung; Lia Lestari (Budapest International Research and Critics University, 2021)
This study aims to determine The Role of Mediator in Industrial Relationship Dispute Settlement Process during Covid-19 Pendemic at Labor Offices Department North Sumatra Province. This research is descriptive research method. The role of the Mediator in the process of resolving industrial relations disputes during the COVID-19 pandemic is the difference of opinion between employees and the company. Can be saidThe role of the Mediator of the Manpower Office is very active in providing guidance on industrial relations, carrying out industrial relations development in the company. This development is technical guidance to entrepreneur workers where the mediator acts as a resource person and is a third person and does not take sides with any of the disputing parties and asks the disputing parties to negotiate before the mediation process is carried out, leads and regulates the course of the mediation session, assists the parties make a collective agreement if an agreement is reached, make written recommendations, and prepare minutes of settlement of industrial relations disputes in accordance with the provisions of Law Number 2 of 2004 concerning Settlement of Industrial Relations Disputes.